Integration of Robotic Education and Islamic Religious Education through the Line Follower Robot Working Model - Hertanti, Erina (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2024)
Designing robotic technology as an innovation to realize more varieties in the learning process is an interesting idea to be implemented in class. This study tries to implement robotic technology innovation into Islamic Religious Education through the line follower robot working model. In this study, the working model is used as an educational media that is implemented within the scope of good morals (al-akhlaq al-mahmudah) and bad morals (al-akhlaq al-mazmumah). This study uses the design-build method to realize the final result as a product. The product design includes designing a guide line for the line follower robot and assembling a line follower robot design system based on the results of device requirement analysis. The results of the implementation of the line follower guide line design are realized on a Flexi paper with a length of 3 meters and a width of 2 meters. While the results of the implementation of the line follower robot design system assembly are in the form of a physical/robot frame, a series of electronic hardware systems, and programs built using C language with the CodeVision AVR compiler. Based on the performance test of the line follower robot, it can be concluded that the overall design system has been successfully realized.